Looting hoards of gold and poaching spotted owls: Data confidentiality among archaeologists & zoologists. Issue 1 (2015) - Frank, Rebecca D.; Kriesberg, Adam; Yakel, Elizabeth; Faniel, Ixchel M.
ABSTRACT: Researchers in the social and health sciences are used to dealing with confidential data, and repositories in these areas have developed mechanisms to prevent unethical or illegal disclosure of this data. However, other scientific communities also collect data whose disclosure may cause harm to communities, cultures, or the environment. This paper presents results from 62 interviews and observations with archaeologists and zoologists. It focuses on how researchers' perceptions of potential harm influence attitudes about data confidentiality, and how these, in turn, influence opinions about who should be responsible for managing access to data. This is particularly problematic in archaeology when harm is not to a living individual but is targeted at a community or culture that may or may not have living representatives, and in zoology when an environment or a species may be at risk. We find that while both archaeologists and zoologists view location information as highly important and valuable in facilitating use and reuse of data, they also acknowledge that location should at times be considered confidential information since it can be used to facilitate the destruction of cultural property through looting or decimation of endangered species through poaching. While researchers in both disciplines understand the potential dangers of allowing disclosure of this information, they disagree about who should take responsibility for access decisions and conditions.